PENGARUH BRAND NAME DAN COUNTRY OF ORIGIN TERHADAP PERSEPSI KUALITAS DAN NIAT BELI MINUMAN RINGAN BERKARBONASI - Adhi Prakosa (Jurnal Manajemen, 2017)
This study aims to test relationships between brand name and country of origin. Independent variable is brand name and country of origin. The dependent variable is perceived quality and intention to buy. The data collection is done directly by using a survey questionnaire. Hypothesis testing is done using simple regression with SPSS version 22.0. Results can be concluded that brand name and country of origin affect the perception of quality to the product and consumer purchase intention.